TRPV4 and the paradox of faster cellular migration rates in more viscous extracellular fluids. (January 2023) - So, Choon Leng; Robitaille, Mélanie; Monteith, Gregory R
Highlights: Cancer cells are subjected to physical stimuli. Cells migrate faster at higher viscosity. Higher viscosity results in Na + / H + exchanger 1 (NHE1) polarization. Activation of TRPV4 through NHE1-induced cell swelling promotes cell migration. Ca 2+ signaling pathways have roles in cancer cell migration. Graphical abstract: Image, graphical abstract